Formative research for the development of an appropriate, acceptable and feasible intervention aimed at reducing type 2 diabetes risk in disadvantaged women after gestational diabetes in South Africa - Muhwava, Lorrein Shamiso (Department of Medicine, 2022)
Background Gestational diabetes mellitus (GDM) is one of the most common obstetric complications, affecting 18.4 million live births globally. In South Africa, the high prevalence of GDM estimated to be up to 25.8%, is driven by the high rates of obesity. Women with a history of GDM have a seven-fold increased lifetime risk of developing type 2 diabetes. In addition, children born of women with GDM are susceptible to impaired glucose tolerance and obesity in adulthood. Prioritising GDM as a public health issue is critical for improving maternal and child health care services and non-communicable disease prevention efforts. There is consistent evidence demonstrating that, in at-risk populations, lifestyle change can reduce the risk of developing type 2 diabetes and among women with GDM, continuation of lifestyle changes after a GDM pregnancy can prevent progression to type 2 diabetes. Understanding women's lived experiences and views around GDM is critical for the development of behaviour change interventions. Further, insights from women's experiences of the healthcare system for GDM care are important for informing health policy and improving the quality of care. At present, little is known about the policies and practices relating to the management of GDM in low- and middle- income countries and health systems interventions that support and facilitate continuity of care are lacking. This thesis constitutes the formative research for a complex intervention study aimed at developing and evaluating a novel health system intervention to reduce the subsequent risk of developing type 2 diabetes among women with GDM. The findings will inform the planning, development and testing of an appropriate and innovative intervention for women with GDM, to be integrated into existing health services in South Africa. Methods and Results The first study used document reviews of policy documents and clinical practice guidelines for the management of GDM in South Africa and 11 key informant interviews with policy makers, health service managers from the Department of Health and clinicians working in the public health services to explore the existing policies and reported clinical practices relating to antenatal and postnatal care for women with GDM in the public health sector in South Africa and identified important factors in delivering an integrated mother - baby postpartum health service. We found that the management of GDM in South Africa is aligned with international standards, in addition to locally developed guidelines and protocols for clinical practice. Our findings also confirmed that postpartum follow-up for women with GDM is a significant problem in South Africa as a result of fragmentation of care and the absence of standardised postnatal care services. Key informants also raised patient – related challenges including lack of perceived future risk of developing type 2 diabetes and non-attendance for postpartum follow up, as barriers to postnatal care for women with GDM. The second study was a descriptive qualitative study which explored the lived experiences of 35 women with prior GDM using content analysis and the COM-B model to identify factors influencing lifestyle change during and beyond the GDM pregnancy. The results suggest that the COM-B model's concepts of capability (knowledge and skills for behaviour change), opportunity (resources for dietary change and physical activity) and motivation (perception of future diabetes risk) are relevant to lifestyle change among women with GDM in South Africa. The third study was an in- depth exploration of women's lived experiences of GDM, their context and perceived needs. Women discussed the emotional and psychological burden of having GDM, highlighting (i) their initial emotional reactions to receiving a GDM diagnosis, (ii) their experience of adjusting to the constraints of living with GDM (iii) their feelings of apprehension about childbirth and their maternal role and (iv) their feelings of abandonment in the post-partum period once the intensive support from both health system and family ends. The fourth study further explored women's perspectives of and satisfaction with GDM care in the public health sector as well as their views on the feasibility and acceptability of the proposed intervention using the Donabedian's quality of care framework. Key sub-themes relating to ‘structure' of care were the organisation of GDM health services, efficiency of the referral, efficiency of management practices, quality of hospital facilities and services and the availability of adequate healthcare resources. Overall satisfaction with GDM care processes was influenced by women's unmet need for education and behaviour change counselling, interpersonal support from health care providers and peers and the health services' capacity to enable them to actively participate in their care. Conclusion The management of GDM is currently foetal - centric and over-medicalised, focusing on clinical care processes to achieve glycaemic control and safeguard foetal health. There is a critical need for woman-centred approaches to be incorporated in the management of GDM in order to improve women's overall experiences of care. Behaviour change interventions for women with GDM should target factors within the physical and social environments, that influence women's capacity for lifestyle change. In addition, we recommend routine mental health and psychosocial vulnerability screening and monitoring for women diagnosed with GDM throughout pregnancy and postpartum to improve prognoses. Finally, holistic interventions and health policies that directly support continuity of care are urgently needed if high rates of progression to type 2 diabetes in this population are to be avoided.